Tingkat Kesejahteraan Keluarga Buruh Tani Wanita pada Bidang Produksi Kopi di CV. Frinsa Agrolestari - Muthiah Syakirotin; Anne Charina (Jurnal Ilmu Pertanian Indonesia, 2020)
Farmworkers in the coffee production section at CV. Frinsa Agrolestari are dominated by women, namely 9 women and 5 men. While the coffee production process is fairly heavy, female farmworkers continue to become workers in this company. The large number of females as farm workers can be caused by the low income in her family. Inadequate income from her husband salary will encourage some of the wifes to get additional income. This research was motivated by this phenomenon. The purpose of this study was to determine the level of welfare of female farmworker families, the contribution of female farmworkers income to the family income, and the motivation of female farmworkers working in the production field at the coffee factory of CV. Frinsa Agrolestari, Margamulya Village, Pangalengan, Bandung Regency. The approach taken in this research was a qualitative approach, using a case study with interviews based on indicators of family welfare levels according to the regulation of BKKBN in the year of 2005. The results of the study showed that the family welfare level of a female working in the field of coffee production at CV. Frinsa Agrolestari was in the Prosperous Family category I indicating that the income can fulfill basic needs such as clothing, shelter, health, and education. Contribution of income of female farmworkers to the family income ranged from 22.2% (the lowest) to 50% (the highest). Motivation of the female farmworkers to work is 89% due to economic reasons and 11% due to social reasons. Keywords: family, farm, labor, welfare,women